HUBUNGAN AIR DAN TANAMAN DIPELAJARI SECARA TERINTEGRASI DENGAN MODEL SIMULASI DINAMIK - Nuril Hidayati (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Water is the most crucial factor in affecting plant growth and production.In order to assess the complex relationship between plant and water,a dynamic model of crop growth was constructed by interlinking plant growth and soil water models.The growth model mainly consists of physiological processes, i.e.photosynthesis, respiration, partitioning, leaf growth and phenological development.The photosynthesis and partitioning models are based on SUCROS, extended in two ways, the calculation of light use efficiency as a function of air temperature and extinction coefficient as a function of LAI.The development model was calculated based on thermal time concept.Water balance model comprises evaporation and transpiration as water losses, and rainfall and irrigation as water sources at 1 m - depth. Evaporation was based on Penmann Monteith formula.Both models were linked by relating the degree of growth reduction to water deficits. Simulation results showed a good agreement with observed data in predicting soil water deficits and crop water use for all of the treatments, i.e.irrigated, irrigated just after flowering, dry and rainfed.Despite the model predicted soil water considerably well, it tent to overestimate soil water deficits in the beginning of the growing period for both years. The results also showed a good agreement between simulated and observed dry matter production,especially under irrigated and rainfed conditions.